Inventory of Natural Orchid Species in Sungai Pelaik Melemba Village Corseving Area at Danau Sentarum National Park Batang Lupar District Kapuas Hulu Regency - YERIKHO JIMMY KURNIAWAN; Agustina Listiawati; Rahmidiyani Rahmidiyani (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT Inventory of natural orchid species (Orchidaceae) is activity to record the data whether there is the presence and absence of orchid itself and also to find out the current existing species and it has economic value to communities. Orchid is a potential biological plant. This flower that is well-know as wilderness gem is a flowering plant which has diverse types, both colors, shapes and all part of the plant. Diversity of these Orchids that in habitat in West Kalimantan will gradually come to extinction and scarcity if they are ignored. Therefore, it must take a real further preservation and expansion toward these Orchids. The purpose of this study is to inventory natural orcid species in Sungai Pelaik, Melemba Village, conserving area at Danau Sentarum National Park, Batang Lupar District, Kapuas Hulu Regency. The research method used was purposive sampling namely, which is a withdrawal sample technique done based on the objective or the problem of the study. The sampling technique uses the path method to explore the research area of 10 ha. The result of this study found 26 species of orchid, consists of 25 types of epiphytes and 1 type of terrestrial.Keyword: Inventory, Orchid, Kapuas Hulu Regency